How to read Daniel - Longman, Tremper (Downers Grove, Illinois IVP, an imprint of InterVarsity Press, 2020)
"Failing to read Daniel well means missing a critical part of God's message to us. Orienting readers to a proper engagement with Daniel, Old Testament scholar and teacher Tremper Longman III examines the book's genre, structure, historical background, and major theological message before diving deeper into each of the stories and visions"--
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc